Alginates: 20000 applications of submarine algae - Ayarza-León, Jorge Luis (2014)
Since antiquity, mankind has depended on the sea to obtain valuable resources. Marine brown algae from the class Phaeophyceae are the source of a biopolymer with very interesting properties called alginate. Nowadays, alginate is extracted and commercialized around the world, it is an essential component in many everyday products, and it is even used in academic research.